Analysis of the Effectiveness of the Application of Restorative Justice in Criminal Cases in Indonesia - Rifqi Alif Darmawan; Muhammad Mahesa Rizki Diputra; Alip Rahman; Anom Sutrisno (Riviera Publishing, 2024)
This research examines the application of restorative justice in Indonesia's criminal justice system, focusing on analyzing its effectiveness in resolving criminal cases. This research aims to examine the application of restorative justice in the criminal justice system in Indonesia, with a focus on analysing its effectiveness in resolving criminal cases. Restorative justice emphasizes victim recovery, offender responsibility, and community reconciliation as an alternative to the traditional punishment-based retributive approach. The research method used is a normative legal study with a qualitative approach and secondary data from a literature review, including books, scientific journals, research reports, and official documents. The research findings show that restorative justice has been successfully applied in several cases, especially minor crimes, with more satisfactory outcomes for victims and better offender rehabilitation. However, there are obstacles, such as limited resources, lack of community understanding, and challenges in the mediation process. Training for mediators, increased public awareness, and supportive policy changes are recommended to improve its effectiveness. The implications of this research indicate the need for legal reforms to integrate restorative justice more broadly in the criminal justice system in Indonesia in order to create a more just and sustainable legal environment.